Penerapan Metode Exponential Smoothing Pada Sistem Informasi Peramalan Stok Bahan Bangunan di PT. Muara Dua Palembang - Deayu Dwi Wiranti; Dhamayanti Dhamayanti (Jurnal Informatika Global)
PT. Muara Dua Palembang is a mobile distributor company in the field of material sales. The number of sales transactions will be affect the inventory of goods, as a company in the field of sales often having problems in predicting the number of items that must be available for the following month. Therefore the need for a system forecasting information that will make it easier for an inside manager make a decision in determining how many items will be ordered kepbarik for the sale of the next period, so it can avoid the effects of prolonged losses. Number forecasting The stock inventory is calculated using the Single method Exponential Smoothing, the data used for this study is sales data for stirrups measuring 19 mm x 12 mm in 2015 up to 2018. After that, data analysis is performed by calculating forecasting use alpha 0.1, 0.45, and 0.9 parameters and calculate the values of the accuracy of forecasting to find out the smallest error. From the calculation results that have been made the most error value small is at alpha 0.9 with MAE = 12 and MSE = 280. The expected results in this study are information systems Forecasting items that have a functioning forecasting form to forecast the amount of demand for goods in the period to become with a Single Exponential Smoothing calculation so it can be used to determine how many items must be prepared to meet costumer demand for the next peridot. Keywords: Forecasting, Single Exponential Smoothing, Stock Items